1980
DOI: 10.1002/1097-0142(19801001)46:7<1705::aid-cncr2820460734>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of breast carcinoma II: Factors related to the predominance of left-sided disease

Abstract: A study of the laterality of 980 patients with unilateral breast carcinoma revealed a leftiright ratio of 1.26. Detailed analysis disclosed a significant association between left predominance and the following clinico-pathologic features: menarche after age 13, age at diagnosis, parity especially among those between ages 40 and 54, and all histologic types except medullary tumors. When asynchronous bilateral carcinoma was documented, the disease first occurred more often in the left breast. Patients with simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
3
2

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 19 publications
(8 reference statements)
1
40
3
2
Order By: Relevance
“…The reason of increased risk in left breast is unclear (Weiss et al, 1996) but few studies have shown a possible correlation with relatively larger left breast size (Ing et al, 1997), unilateral lactation (Ing et al, 1997), detection biased due to predominant right handedness (Perkins et al, 2004) or more denser left breast (American Cancer Society, 2011-12). This study also revealed that women having right breast cancer were younger than those having left sided disease and this concurs with various published studies showing left sided laterality is more pronounced at higher ages (Busk, 1947;Garfinkel et al, 1959;Senie et al, 1980). Interestingly in this study, patients with right sided disease had smaller primary tumor size and were more prone to have triple negative as well as isolated ER, PR and Her2-Neu negativity.…”
Section: Discussionsupporting
confidence: 91%
“…The reason of increased risk in left breast is unclear (Weiss et al, 1996) but few studies have shown a possible correlation with relatively larger left breast size (Ing et al, 1997), unilateral lactation (Ing et al, 1997), detection biased due to predominant right handedness (Perkins et al, 2004) or more denser left breast (American Cancer Society, 2011-12). This study also revealed that women having right breast cancer were younger than those having left sided disease and this concurs with various published studies showing left sided laterality is more pronounced at higher ages (Busk, 1947;Garfinkel et al, 1959;Senie et al, 1980). Interestingly in this study, patients with right sided disease had smaller primary tumor size and were more prone to have triple negative as well as isolated ER, PR and Her2-Neu negativity.…”
Section: Discussionsupporting
confidence: 91%
“…Such changes could take place more readily over a prolonged "resting" period, as in the breasts of the perpetual nullipara. We have no explanation for the difference of response according to laterality, but emphasize that this is the first objective evidence that the breasts may differ in their parenchymal behaviour, despite previous exhaustive comparisons for such a distribution on other grounds (Senie et al, 1980).…”
Section: Discussioncontrasting
confidence: 56%
“…Although modest with a ~1.10 left/right incidence ratio, such laterality was consistently found in several epidemiological studies [3036] regardless of gender and stage of disease. Even in bilateral breast cancer cases, the left breast is more frequently affected first, or with a larger tumor [37]. …”
Section: Left-right Asymmetry In Breast Cancermentioning
confidence: 99%
“…A variety of epidemiological correlates have been investigated, including age, race, ethnicity, sex, breast size, stage of disease at diagnosis, histological tumor type, and even left- versus right-handedness. None of these factors emerged as a consistently significant variable for the increased left-sided incidence [30–32, 37]. By contrast, laterality in outcome may in part be explained by laterality of axillary lymph node metastasis.…”
Section: Left-right Asymmetry In Breast Cancermentioning
confidence: 99%